Cost-effectiveness and return on investment of hepatitis C virus elimination in China: A modelling study - Meiyu Wu; Jing Ma; Xuehong Wang; Sini Li; Chongqing Tan; Ouyang Xie; Andong Li; Aaron G Lim; Xiaomin Wan (Clinical and Molecular Hepatology)
Background/Aims The World Health Organization set the goal of eliminating hepatitis C virus (HCV) by 2030, with 80% and 65% reductions in HCV incidence and mortality rates, respectively. We aimed to evaluate the health benefits, cost-effectiveness and return on investment (ROI) of HCV elimination. Methods Using an HCV transmission compartmental model, we evaluated the benefits and costs of different strategies combining screening and treatment for Chinese populations. We identified strategies to achieve HCV elimination and calculated the incremental cost-effectiveness ratios (ICERs) per disability-adjusted life year (DALY) averted for 2022–2030 to identify the optimal elimination strategy. Furthermore, we estimated the ROI by 2050 by comparing the required investment with the economic productivity gains from reduced HCV incidence and deaths. Results The strategy that results in the most significant health benefits involves conducting annual primary screening at a rate of 14%, re-screening people who inject drugs annually and the general population every five years, and treating 95% of those diagnosed (P14-R4-T95), preventing approximately 5.75 and 0.44 million HCV infections and deaths, respectively, during 2022–2030. At a willingness-to-pay threshold of $12,615, the P14-R4-T95 strategy is the most cost-effective, with an ICER of $5,449/DALY. By 2050, this strategy would have a net benefit of $120,997 million (ROI=0.868). Conclusions Achieving HCV elimination in China by 2030 will require significant investment in large-scale universal screening and treatment, but it will yield substantial health and economic benefits and is cost-effective.